Ethical Position of Somatic Gene Therapy in Human: A Propose Model of Shari’ah Framework - Zakiah Samori, Fadilah Abd Rahman (International Journal of Advanced Science and Technology, 2020)
The rapid progress of medical and biotechnology science including human genetic technology gives hope in the treatment of some acquired genetic disease. This include Somatic Gene Therapy clinical application which has entered clinical trial in some developed countries. Review from the academic priory literatures demonstrate that this recent therapy offers potential therapeutic treatment for various inherited genetic disorders, certain malignancies and infectious diseases in human at the early stage. Thus it is believed that it will become part of medical practice in the future. However, as other medical treatment, this hopes has been accompanied with several contentious issues and societal concerns from the ethical and religious point of view. Therefore, the acceptability of conducting Somatic Gene Therapy clinical application is evaluated from the Islamic perspective. By this evaluation, this study intends to propose a comprehensive model of the Shari’ah framework dedicated for Somatic Gene Therapy clinical application after the detail discussion from the Shar’iah resources are carried out. In this intense review, potential application as well as various ethical issues related to Somatic Gene Therapy are firstly examined. The legality of conducting this therapy is also discussed according to the detailed analysis of the interpretation of Qur’anic principles together with the Hadith of the Prophet Muhammad pbuh are appraised. Its ethical position from the views of Maqasid al-Syariyyah (Objective of the Shari’ah) and the Qawa’id Fiqhiyyah (Islamic Legal Maxims) are then critically analysed and various fatwas (Islamic verdict) from the fatwa councils from all over the world are also outlined. This model of Shariah Framework would serve as the ethical guidelines and facilitate the medical practitioners, scientist and physician in the decision- making of Somatic Gene Therapy clinical practice especially in Malaysia and beyond (particularly Muslim countries). This study further concludes that Somatic Gene Therapy for therapeutic purposes is permissible with full consideration and all possible precautions are carried out. Therefore, there must be some Islamic legislation to be developed by the competent authorities in any attempt to pursue the permitted treatment of Somatic Gene Therapy in any Muslim countries in the future.